Comprehensive Review on Seismic Facies Identification - Liang, Rui (International Journal of Computer Science and Information Technology, 2024)
Seismic facies identification is crucial for interpreting subsurface geological features and predicting reservoir properties. This review discusses the methodologies, advancements, and applications in seismic facies identification, including traditional approaches, machine learning techniques, and case studies. The aim is to provide a thorough understanding of the current state and future directions in this field.